A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species - Saucier, Esprit Heestand; Sajjadi, Auzita; France, Scott C. (Zootaxa, 2017)
The deep-sea bamboo coral genus Acanella has a cosmopolitan distribution, is found on hard and soft substrata between 300 and 2875 meters depth, and may be abundant where present. The genus has been the source of taxonomic debate almost since its initial description, and species in the North Atlantic have proven difficult to identify. We examined 145 Acanella colonies collected from across a broad geographic distribution to address morphological variation in the context of genetic differences, focusing on the North Atlantic species, but with a comparison to four Pacific species. We generated DNA sequences for mitochondrial mtMutS and nuclear 18S from ninety-seven Acanella specimens. After combining data from both gene regions, eight concatenated sequences were identified (A–H), six of which are associated with nominal species, while the other two come from taxa that do not match any known species description. The most common sequence (A) is associated with specimens identified as Acanella arbuscula, A. eburnea, and Isidella elongata. We find that morphological characteristics used to differentiate these species are distributed along an intraspecific continuum and that alternate morphologies of A. arbuscula have been identified in collections as different species, with the identity influenced by sampling location. We synonymize A. eburnea with A. arbuscula and discuss confusion with I. elongata. The geographic range of A. arbuscula is expanded. We propose the resurrection of the Mediterranean species A. furcata and describe two new species, A. aurelia sp. nov. and A. scarletae sp. nov. New geographic records and the first SEM images of the Pacific species A. chiliensis, A. rigida, and A. robusta, all described prior to 1907, are also presented.